The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fphys.2020.00907
|View full text |Cite
|
Sign up to set email alerts
|

Training Induced Changes to Skeletal Muscle Passive Properties Are Evident in Both Single Fibers and Fiber Bundles in the Rat Hindlimb

Abstract: Introduction: The passive mechanical behavior of skeletal muscle represents both important and generally underappreciated biomechanical properties with little attention paid to their trainability. These experiments were designed to gain insight into the trainability of muscle passive mechanical properties in both single fibers and fiber bundles. Methods: Rats were trained in two groups: 4 weeks of either uphill (UH) or downhill (DH) treadmill running; with a third group as sedentary control. After sacrifice, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“… Noonan et al (2020) demonstrated this with lower passive stress and passive elastic modulus in soleus single fibres of rats that ran downhill compared to uphill. Noonan et al (2020) used the same rats as Chen et al (2020) , therefore these lower passive properties appeared to be due to a 6% greater SSN.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“… Noonan et al (2020) demonstrated this with lower passive stress and passive elastic modulus in soleus single fibres of rats that ran downhill compared to uphill. Noonan et al (2020) used the same rats as Chen et al (2020) , therefore these lower passive properties appeared to be due to a 6% greater SSN.…”
Section: Discussionmentioning
confidence: 76%
“…With a greater SSN, individual sarcomeres may stretch less during muscle excursion, leading to less passive force generated by sarcomeric proteins such as titin (Herbert and Gandevia, 2019). Noonan et al (2020) demonstrated this with lower passive stress and passive elastic modulus in soleus single fibres of rats that ran downhill compared to uphill. Noonan et al (2020) used the same rats as Chen et al (2020), therefore these lower passive properties appeared to be due to a 6% greater SSN.…”
Section: Did Weighted Downhill Running Training Induce Sarcomerogenesis?mentioning
confidence: 94%
“…Noonan et al (2020) demonstrated this with lower passive stress and passive elastic modulus at longer SLs in soleus single fibers of rats that ran downhill compared to uphill. Noonan et al (2020) used the same rats as Chen et al (2020), therefore the lower passive stress and elastic modulus appeared to be due to a 6% greater SSN.…”
Section: Discussionmentioning
confidence: 72%
“…With a greater SSN, individual sarcomeres may stretch less during muscle displacement, leading to less passive force generated by sarcomeric proteins such as titin (Herbert and Gandevia, 2019). Noonan et al (2020) demonstrated this with lower passive stress and passive elastic modulus at longer SLs in soleus single fibers of rats that ran downhill compared to uphill. Noonan et al (2020) used the same rats as Chen et al (2020), therefore the lower passive stress and elastic modulus appeared to be due to a 6% greater SSN.…”
Section: Did Sarcomerogenesis Impact Force-length Relations?mentioning
confidence: 92%
“…Owing to the abundant water content and highly oriented muscle fibers, skeletal muscles exhibit outstanding physical properties, such as good fatigue resistance, high mechanical strength, excellent flexibility, and so forth. , Although some features of skeletal muscles in conductive hydrogels have been successfully imitated through various methods, it is still impossible to reproduce all the desired properties in one material system. , Liang et al designed a strategy to fabricate hydrogels with preferentially aligned micro/nanostructures, which endowed the hydrogel with a more than 100-fold increase in fatigue thresholds. The prepared fatigue-resistant hydrogels were alternatives to soft materials in robots and artificial muscles .…”
Section: Introductionmentioning
confidence: 99%